NS reassortment of an H7-type highly pathogenic avian influenza virus affects its propagation by1 altering the regulation of viral RNA production and anti-viral host response - Wang, Zhongfang; Justus Liebig University Giessen (My University, 2010)
Since 1997 the emergence of H5-type highly pathogenic avian influenza virus (HPAIV) hasresulted in major losses to the poultry industry and caused over 500 human infections withapproximately 60% mortality. In Europe H7-type HPAIV have been circulating for a longtime with very little pathogenicity for humans. Nevertheless, the ability of influenza viruses(IV) to mix their segmented genomes upon double infections could lead to the emergence ofnew, reassortant H7-type HPAIV with altered characteristics that could pose an additionalthreat to humans. The viral NS segments encoding the NS1 and NS2/NEP proteins can affectthe anti-viral host responses, inhibit cellular mRNA processing and enhance viral mRNAtranslation. NS1 contributes to high virulence and host range variation and it was reported thatNS segments of H5-type HPAIV isolated after 1998 can enhance replication of human IVreassortants in mammalian cells. Still it is not clear how the NS allele type, the subtype andthe year of isolation of the parental virus affects host range, genome replication/transcription,viral propagation and pathogenicity of an H7-type reassortant.In order to elucidate several of these important questions reassortant A/FPV/Rostock/34(H7N1) HAPIV with NS segments from H5- and H7-type avian IV strains were generated byreverse genetics. Virological characterizations demonstrated that growth kinetics of thereassortant viruses differed from the wild type FPV and depended on the mammalian or avianorigin of the infected cells. Surprisingly, the different reassortant NS segments were not onlyresponsible for alterations in the anti-viral host response, but furthermore affected viralgenome replication/transcription and its intra-cellular transport. Further experimentsdemonstrated that the effects on accumulation of viral RNA species depended on the specificNS-segment as well as on the genetic background of the viral polymerase. IFN-betaexpression and apoptosis induction were found to be inversely correlated to viral growth,while the NS allele, virus subtype and NS1 protein expression levels showed no correlation.Even though it is likely that the multiple effects of the NS1 protein act on many viral and hostprocesses as why one can not conclude which of the effects is the most important for the viralreplication ability, these results demonstrate that the origin of NS segment can affect thereplication efficiency, host range and pathogenicity of H7-type HPAIV.

Seit 1997 führt das Auftreten von hoch pathogenen aviären Influenza Viren (HPAIV) des H5-Subtyps zu schweren Verlusten in der Geflügelindustrie und verursachte bislang über 500humane Infektionen mit über 60% Mortalität. In Europa zirkulieren H7-Subtyp HPAIV seitlangem, allerdings mit niedriger Pathogenität für den Menschen. Gleichwohl könnte dieFähigkeit von Influenza Viren (IV) ihr segmentiertes Genom bei einer Doppelinfektion zuvermischen (reassortieren) zu neuen H7-Typ HPAIV mit neuen Eigenschaften führen, dieevtl. eine Gefahr für den Menschen darstellen. Das NS-Segment, welches für das NS1- undNS2/NEP-Protein kodiert, teilt sich in zwei Alleltypen auf (Aund B). Es kann sowohl die antiviraleWirtsantwort beeinflussen und die zelluläre mRNA-Prozessierung hemmen, als auchdie Translation viraler mRNA fördern. NS1 trägt zu erhöhter Virulenz und Änderung desWirtsspektrums bei und es wurde berichtet, dass NS-Segmente von H5-Typ HPAIV, welchenach 1998 isoliert wurden, die Vermehrung humaner IV in Säugerzellen erhöhten können.Dennoch ist nicht klar, wie der NS-Alleltyp, der Subtyp und das Jahr der Isolation desparentalen Viruses das Wirtsspektrum, die Genom-Replikation/Transkription, dieVirusvermehrung und Pathogenität einer H7-Typ Reassortante beeinflußt.Zur Beantwortung dieser wichtigen Fragen wurden mittels reverser Genetik verschiedenereassortante A/FPV/Rostock/34 (H7N1) HPAIV mit NS-Segmenten von aviären H5- und H7-Typ IV-Stämme erstellt. Virologische Charakterisierung zeigte, daß die Wachstumskinetikender reassortanten IV sich vom wild Typ FPV unterscheiden und davon abhängen, ob SäugeroderVogelzellen infiziert worden waren. Überraschender Weise waren die verschiedenen NSSegmentenicht nur für Änderungen der anti-viralen Wirtsantwort verantwortlich, sondernbeeinflußten außerdem die virale Genom-Replikation/-Transkription und dessen intrazellulärenTransport. Weitere Experimente demonstrierten, daß die Effekte auf dieAkkumulation der viralen RNA-Species sowohl von den spezifischen NS-Segmentenabhingen, als auch von dem genetischen Hintergrund der Viruspolymerase. IFN-beta-Expression und Apoptose-Induktion waren entgegengesetzt zur Virusvermehrung, wogegendas NS-Allel, der Virussubtyp und das Maß der NS1-Expression keine Korrelation zeigten.Obwohl es wahrscheinlich ist, dass die Vielzahl der Effekte von NS1 sich auf viele Virus- undWirtsprozesse auswirken, wodurch es auch nicht möglich ist den wichtigsten Effekt für dieVirusvermehrung zu definieren, zeigen diese Ergebnisse das der Ursprung des NS-Segmentsdie Vermehrungseffizienz, das Wirtsspektrum und die Pathogenität von H7-Typ HPAIVbeeinflussen kann.
Reassortierung eines hoch pathogenen aviären Influenzavirus (H7-Typ) beeinflusst dessen Vermehrung durch Änderung der viralen RNA-Produktion und der angeborenen Immunität
Keywords: ddc:610